2011
DOI: 10.1111/j.1540-6237.2011.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Context and Immigration Policy Preferences Among Latinos and Anglos*

Abstract: Objective. We examine how the immigration policy preferences of Anglos and Latinos vary according to ethnic context. Specifically, we hypothesize that immigration policy attitudes are a product of both Latino immigrant and Latino native born group size. In contrast to previous work, which found that Latinos and Anglos react to contextual forces in an identical manner, we argue that Latino group size produces opposite reactions for Anglos and Latinos. Methods. These hypotheses are tested using an original sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 27 publications
6
51
0
Order By: Relevance
“…Yet both demographic context (at various levels of aggregation) and social contact with illegal immigrants (both positive and negative) might also influence how people weigh immigrant attributes (e.g. Berg 2009;Hopkins 2010;Rocha et al 2011). Media exposure, too, could play this role depending on the extent and tone of coverage on the issue (Dunaway et al 2010;Valentino et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Yet both demographic context (at various levels of aggregation) and social contact with illegal immigrants (both positive and negative) might also influence how people weigh immigrant attributes (e.g. Berg 2009;Hopkins 2010;Rocha et al 2011). Media exposure, too, could play this role depending on the extent and tone of coverage on the issue (Dunaway et al 2010;Valentino et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that we cannot test the specific conditions of the UIMGC, we use it as a guiding perspective toward understanding some of the dynamics associated with views toward immigrant groups. methodoLogy We hypothesize that student-level variables influence views toward undocumented immigrants' access to public education, considering the body of literature and theory that has identified individual demographics (e.g., Brader et al, 2010;Esses et al, 2005;Palmer & Davidson, 2011) and precollege experiences, such as residential context (Rocha et al, 2011), as significant predictors of views regarding immigration policy. Furthermore, the wealth of scholarship devoted to understanding the impact of college (Astin, 1993;Pascarella & Terenzini, 2005) points to the association of many educational experiences with less restrictive views (Janus, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The Pew Research Center (2006) reveals that 55% of Phoenix residents view immigration as a "very big" community problem versus 19% of Chicago residents. These metropolitan differences may have to do with the concentration of immigrants, both documented and undocumented, living in different parts of the country (Hanson, 2005;Hood, Morris, & Shirkey, 1997;Rocha et al, 2011), but could also be due to the differences in political discourse within these residential areas. These findings suggest that the social environments in which individuals live and interact have an influence on attitudes toward immigration.…”
mentioning
confidence: 96%
“…Access to public education for undocumented immigrants continues to be a highly polarized issue with recent national opinion polls showing that a large proportion of Americans continue to oppose access for these students (Bushaw and Calderon 2014;Pew Research Center 2014), while other research demonstrates that higher levels of education are consistently associated with more supportive views on immigration (Fennelly and Federico 2008;Pérez 2010;Pew Research Center 2006). Although research has shown that public opinions regarding immigration legislation are linked to political, demographic, and economic contexts (i.e., Hanson 2005;Rocha et al 2011;Sobczak 2010), there is a dearth of empirical studies on how these various contexts at multiple levels (i.e., institutional and state) influence US citizen students' attitudes about immigration during the college years, an important developmental period where students' perspectives and views evolve. Given their roles in the voter base, the employment market, residential selection, as well as the college campus itself, an examination of how political, economic, and demographic contexts affect US citizen college students' attitudes towards undocumented immigrant educational access is particularly important, especially since national opinion polling may not capture the college contexts or individuals of interest to higher education researchers, practitioners, and policymakers.…”
Section: Introductionmentioning
confidence: 99%